A promoção da saúde na escola e sua relação com o uso de drogas pelos estudantes - Pinto, Raquel Oliveira (Universidade do Vale do Rio dos Sinos, 2013)
In recent times psychoactive drugs have been posing an important challenge to public healthcare. The early age of the first contact with them, mainly among school age children and adolescents, highlights the need of preventive policies directed to this population. Prevention programs in this area are more effective when comprised of multiple approaches, integrating institutions and diverse segments of society. Since the mid 1990s, health promotion in school environment worldwide has been guided by a fundamental effort to develop and enable healthier school environments in a very broad sense. This study aimed firstly to investigate the relationship among different conditions that promote health related to structure, resources and actions, found in schools in two medium-sized municipalities in the state of Rio Grande do Sul, and the use of psychoactive substances among students. In face of the absence of a validated instrument for assessing school environment in Brazil and the limitations inherent to a master’s thesis, the development and validation of an instrument to assess health promotion initiatives in schools was chosen as the focus of this study. A further stage of the study will contemplate the relationship between this variable and the behaviors associated to the use of psychoactive drugs. In this thesis the following phases were covered: literature review and reading of national and international documents and guides relevant to the subject studied, including the “Programa Saúde na Escola”; formulation of an instrument with 60 items based on the results obtained in the first phase; validation of the items’ content according to the Delphi technique, supported by five regional and national specialists in school health promotion; application of the instrument in 53 schools, both public and private, in the municipalities of Sapiranga and Lajeado, both located in the countryside of the state of Rio Grande do Sul, Brazil; validation of the instrument through reliability and principal components analyses. The dimensions resulting from these analyses included educational, structural, and relational aspects within school environment, either by direct observation or information provided by school managers. Data related to this study will be submitted to publication in an article named “Desenvolvimento e validação de um instrumento de avaliação de promoção de saúde na escola” (Development and validation of an instrument for the assessment of health promotion in school environment).
Keywords: Promoção de saúde; Saúde escolar; Avaliação; Health promotion; School healthcare; Assessment; ACCNPQ::Ciências da Saúde::Saúde Coletiva